Validation of a 5-DoF instrumented speed skate; towards a power meter for speed skating - van der Eb, J. W.; Veeger, D.; de Koning, J. (ISBS Proceedings Archive (Michigan), 2020)
Speed skates are the most important part of equipment of a speed skater, where weight, rocker and bend are just a few characteristics that are to a high degree individualized. This poses a challenge for any type of research in speed skating where forces have to be measured in a reliable manner. For this purpose, a 5 degrees of freedom (DoF) instrumented speed skate (VU-Skate) has been designed and validated, weighing only 130 gram extra. Skaters use their own blades and shoes, something skaters are very keen on. A calibration tool has been developed to calibrate the 5 DoF. The quality of the data has been validated in 2 ways: 1. With the use of force plates and 2. By comparing the signals to another (also newly developed) Ultra-light Forces sensor. The results are remarkably good. This is the first step in being able to measure power continuously during each stroke.